'Bloom in the Desert': American Society for Indexing Annual Conference 2019. (September 2019) - Millis, Kendra
Abstract : Kendra Millis reports on the American Society for Indexing (ASI) conference, held in Scottsdale, Arizona, 25–7 April 2019.